Determinants of Pre-Pandemic Demand for the IMF's Concessional Financing. (IMF Working Papers; Working Paper, 2021)
This study focuses on identifying the main factors that influenced country-specific and aggregate demand for IMF concessional financing between 1986 and 2018 and makes within-period and out-of-period forecasts. We find that the external debt level, inflation, and real effective exchange rate are the main economic variables influencing concessional borrowing for most eligible countries. Finally, our approach is able to provide quite accurate country-level and aggregate forecasts for historical financing events prior to the COVID-19 pandemic.